Vaccine immunity. - Beverley, P (1997)
A recent meeting on vaccine immunity focused on the key issue that confronts immunologists in developing a new generation of vaccines: how to initiate powerful and long-dived immune responses without stimulating excessive inflammation or autoimmunity.